PENGARUH KADAR PEREKAT TERHADAP SIFAT PAPAN PARTIKEL AMPAS TEBU - M. I. Iskandar; Achmad Supriadi (BRIN Publishing, 2013)
Particleboards as one kind of the reconstituted wood products in their manufacture still rely on the Sonventional wood material from natural forest, which in potency becomes limited and scarce. Consequently, use of alternative woods or other ligno-cellulosic fibrous stuffs deserves thorough consideration, with their potency abundant and mostly still unutilized, such at bagasse (sugar-cane fibers) waste from sugar factories. In relevant, a research on particle board manufacture avus conducted using bagasse particles bonded together with urta-formaldehyde (UF) adhesive. This research aimed to look into the effect of UF content (i.e. 6%, 8%, and 10% based on the dry weight of the particles) on the physical-mechanical properties of the resulting particleboard. Results revealed that increasing the UF content brought about a significant decrease in the thickness swelling and water absorption of the board; and increases in MOR, MOE, and crew-withdrawal strength, but inflicted so significant changes on the moisture content, density, and internal band. Particleboard properties that could favor the standards of consecutively Indoncia (SNI), Japan (JIS) and FAO either entirely or partially were density, moisture content, and MOR. The greatber the UF content, the more of those properties satisfying the JIS spesification. Judging from in density, this experimented particleboard was more suitable for ate at room deathing and frumed table-plane. The particielswars that looks the neust prospective for such purposesmere those ning UF at 8% content.